2004
DOI: 10.1002/mus.20054
|View full text |Cite
|
Sign up to set email alerts
|

Number of contractions to maintain mass and force of a denervated rat muscle

Abstract: Within 5 weeks, denervated extensor digitorum longus (EDL) muscles of rats lose 66% of mass, 91% of force, and 76% of fiber cross-sectional area (CSA). We previously determined the parameters of electrical stimulation for denervated rat EDL muscles to generate tetanic contractions sufficient to maintain mass and force close to control values. Using these parameters, we tested the hypothesis that a range exists for number of contractions per day, below and above which values for mass, maximum force, and fiber C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
2
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 34 publications
3
113
2
13
Order By: Relevance
“…The current intensity was also determined by previous studies where we found the ideal point for muscular contraction. In our literature review, we found studies using intensity ranges from 1 mA to 5 mA , however, these studies used anesthetized rats or implanted electrodes 24,25,27,28,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current intensity was also determined by previous studies where we found the ideal point for muscular contraction. In our literature review, we found studies using intensity ranges from 1 mA to 5 mA , however, these studies used anesthetized rats or implanted electrodes 24,25,27,28,36 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the metabolic effects, ES also helps in minimizing the effects of immobilization, minimizing the reduction of cross-sectional area, interstitial fibrosis and deficiency of blood supply 22 . ES promotes increased effectiveness of contractile muscle fibers, enabling thus the dynamics of uptake via GLUT-4, glucose metabolism and activity of cellular metabolic pathways [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The complete motor function recovery after nerve injury requires the occurrence of morphological and physiological processes that determine the return of motoneurons electrical activity on the involved muscles 9 . The use of muscle electrical stimulation after peripheral nerve injury for the prevention of progressive muscle atrophy, although there is weak evidence that, can be beneficial when applied under favorable conditions 10 . This fact reinforces the importance of controlled trials for the establishment of new treatment strategies to stimulate peripheral nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, LT was not able to reduce the deficit in muscle maximal force and atrophy observed after nerve injury or AChE deficiency, possibly because the program of muscle contractions resulting from LT is not appropriate. 37 We also observed that reduced muscle use aggravated the muscle deficit in maximal force and atrophy after nerve injury. Moreover, we found that LT and muscle disuse did not change muscle functional innervation.…”
Section: Beneficial Effect Of Lt On Fatigue Resistance In Thementioning
confidence: 56%